Relationship between the Korean Version Survey of the Autonomic Symptoms Score and Cardiac Autonomic Neuropathy Parameters in Patients with Diabetic Peripheral Neuropathy - Sun Hee Kim (Diabetes & Metabolism Journal, 2014)
BackgroundThe Survey of Autonomic Symptom (SAS) scale was reported as an easy instrument to assess the autonomic symptoms in patients with early diabetic neuropathy. In this study, we investigated the relationship between the SAS scale and the parameters of cardiac autonomic neuropathy (CAN) in Korean patients with diabetic peripheral neuropathy (DPN).MethodsThe SAS scale was tested in 30 healthy controls and 73 patients with DPN at Chonbuk National University Hospital, in Korea. The SAS score was compared to the parameters of the CAN test and the total symptom score (TSS) for DPN in patients with DPN.ResultsThe SAS symptom score and total impact score were increased in patients with DPN compared to the control group (P=0.01), particularly in sudomotor dysfunction (P=0.01), and vasomotor dysfunction (P=0.01). The SAS score was increased in patients with CAN compared to patients without CAN (P<0.05). Among the diverse CAN parameters, the valsalva ratio and postural hypotension were associated with the SAS score (P<0.05). However, there was no association between the SAS scale and TSS for DPN, and TSS for DPN did not differ between patients with and without CAN.ConclusionSAS is a simple instrument that can be used to assess autonomic symptoms in patients with diabetes and can be used as a screening tool for autonomic neuropathy, particularly for CAN.